The Participation of Wood Based Sector in the Malaysian Research and Development Grant Scheme - Ahmad, Abdul Halim (2003)
Wood based sector has been identified as a major industry contributing towards technological development and advancement in Malaysia with respect to the value of the products made and number of people employed. It plays an important role in increasing Malaysia's exports earnings. However, Malaysian wood based industry is now encountering several problems namely shortage of labour, excess capacity in certain sectors, low level of technology, low recovery rates, low quality products and many more. In 1 990, Malaysia has set up a clear vision i.e. to transform itself into a fully developed nation by the year 2020. The process requires the support of the whole Government machinery, and the private sector is expected to play a bigger role especially in R&D. In meeting the goals of Vision 2020, Malaysia has embarked several policy guidelines such as the Second Industrial Master Plan (1995 - 2005) and established supporting institutional framework for promoting R&D such as research grant schemes and incentives, especially for resource based industry. There are three main research grant schemes related to wood based industry provided by the Government, namely the Industrial Grant Schemes (IGS), the Industrial Technology Acquisition Fund (TAF) and the Engineering Design Grant. This study attempts to determine the participation of private wood-based organisations in the three main grant schemes provided by the Government. A survey involving 70 private companies in wood-based industry has been conducted to evaluate their participation in R&D activity and identify the major constraints hampering them in conducting R&D. The survey shows that only 17 % of the companies are actively carrying out R&D whereas 57.3 % are not engaged in R&D activity and 25.7 % of the companies did not submit any feedback. The survey also indicates that the major factor limiting the participation of private organizations in conducting R&D is lack of R&D personnel.